Tingkat Penerapan Teknologi Pertanian dan Strategi Pengembangan Budidaya Bawang Merah (Allium cepa. L) di Desa Tes Kecamatan Bikomi Utara Kabupaten Timor Tengah Utara - Adrianus Seran; Werenfridus Taena (Fakultas Pertanian, Universitas Timor, 2019)
This study aims to: (1) determine the level of application of shallot cultivation technology in the Tes Village of North Bikomi Subdistrict of North Central Timor Regency, (2) analyze internal and external factors and formulate a strategy for developing shallots farming in the Tes Village of North Bikomi Sub-District in North Central Timor Regency. This research was conducted in the Tes Village in September to October 2018. Data collection used the survey method. Determination of the sample was done by purposive sampling with the consideration of farmers who had cultivated shallots for 3 years in the Tes Village as many as 22 respondents. The analytical tool used in this study is Likert scale analysis and SWOT analysis. The results of the study suggest that the agricultural technology used includes equipment (tractors, cultivators, water motors), and management of onion farming. Likert scale analysis suggests that the percentage of technology use in shallot farming as recommended is 76.38% and 23.38% which is not recommended, so it is categorized as recommended. According to the SWOT analysis, onion farming is grouped in quadrant I, with alternative strategies including first a strategy to increase business capital supported by the government obtains a score (score 5.78), the second strategy for accumulating venture capital from farmers to anticipate increased seed prices (score 5.76). The three training and counseling strategies from field agriculture instructors to improve the quality of human resources farmers (score 3.48).